Application of Acceptance and Commitment Therapy (ACT) in Children and Adolescents Psychotherapy: An Umbrella Review - Gooya Tayyebi; Nathera Hussin Alwan; Ameera Fares Hamed; Alhan Abdulhasan Shallal; Thaiba Abdulrazzaq; Reyhane Khayayi (Iranian Journal of Psychiatry, 2024)
Objective: Acceptance and Commitment Therapy (ACT) is an evidence-based psychological intervention that has gained increasing attention in recent years. While extensively studied for its effectiveness in adult populations, there has been growing interest in exploring the application of ACT in children and adolescents psychotherapy. This umbrella review aims to provide an overview of the current literature on the use and efficacy of ACT in children and adolescents, as well as to highlight potential considerations and future directions for research. Method: A comprehensive search was done in scientific databases, including Scopus, PubMed, and Web of Sciences, using keywords related to ACT, children, adolescents, and psychotherapy. Relevant articles were included, with a focus on systematic reviews and meta-analysis. Results: Our findings indicate consistent effectiveness for ACT and related interventions across various delivery formats, including in-person, group, and internet-based approaches, in reducing symptoms of internalizing and externalizing problems, as well as improving overall quality of life among children and adolescents. However, two articles comparing ACT with traditional cognitive behavioral therapy did not demonstrate superiority. Additionally, when comparing internet-based and in-person delivery modes, the included studies did not show significant differences between the two types. Conclusion: ACT shows promise as an effective therapeutic approach in children and adolescents psychotherapy. However, more research is warranted to establish its specific techniques and adaptations for different age groups and presenting problems. Additionally, future research should explore the feasibility and effectiveness of delivering ACT in varied settings.